2007
DOI: 10.1016/j.joen.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Monoblocks in Root Canals: A Hypothetical or a Tangible Goal

Abstract: The term "monoblock" has become a familiar term in the endodontic literature with recent interest in the application of dentin adhesive technology to endodontics. Endodontic "monoblocks" have generated controversial discussions among academicians and clinicians as to whether they are able to improve the quality of seal in root fillings and to strengthen roots. This review attempts to provide a broader meaning to the term "monoblock" and see how this definition may be applied to the materials that have been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
314
2
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(369 citation statements)
references
References 92 publications
(91 reference statements)
10
314
2
18
Order By: Relevance
“…In addition, the use of Clearfil SE Bond and Clearfil Photocore has been shown in high shear bond strength between the cervical dentin and the composite resin core (28.9 MPa) 23) . Panavia F 2.0 has demonstrated high shear bond strength between root dentin and FRC posts, therefore it was used as a luting agent between the root dentin and the FRC post 24) . A previous study suggested that the use of cast, prefabricated metal posts and with different lengths affected fracture resistance 7) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of Clearfil SE Bond and Clearfil Photocore has been shown in high shear bond strength between the cervical dentin and the composite resin core (28.9 MPa) 23) . Panavia F 2.0 has demonstrated high shear bond strength between root dentin and FRC posts, therefore it was used as a luting agent between the root dentin and the FRC post 24) . A previous study suggested that the use of cast, prefabricated metal posts and with different lengths affected fracture resistance 7) .…”
Section: Discussionmentioning
confidence: 99%
“…The primary purpose of a post is to improve the retention of core materials in case of a significant loss of coronal tooth structure 12) . Those posts with similar elastic modulus to dentin (17 GPa) resulted in a lower incidence of root fracture by acting as a monoblock with dentin 3,32,37) . In this regard, FRC posts seem to have advantages over ceramic and metal posts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the integrity of the final endodontic-restorative continuum mono-block approaches that of the original healthy tooth itself. 11 An additional use of fiber posts is that they help to distribute the stress uniformly to the remaining radicular dentin. The possible postoperative complications include discoloration of the reattached fragment and fracture to labial horizontal forces with new trauma.…”
Section: Discussionmentioning
confidence: 99%